Defect-rich WS2–SPAN nanofibers for sodium/potassium-ion batteries: ultralong lifespans and wide-temperature workability. Issue 4 (24th January 2023) - Lei, Zewei; Zheng, Jingao; He, Xiaotong; Wang, Yiyi; Yang, Xuhui; Xiao, Fuyu; Xue, Hun; Xiong, Peixun; Wei, Mingdeng; Chen, Qinghua; Qian, Qingrong; Zeng, Lingxing
Abstract : The WS2 –SPAN-2 composite was prepared via an electrospinning technology combined with a sulphuration process. It possesses ultralong lifespans and wide temperature range workability. Abstract : Currently, the investigation of two-dimensional (2D) crystalline materials, notably transition metal tungsten-based sulfides, is scarcely reported in the wide-temperature field. Thus, tungsten sulphide encapsulated in a sulphurized polyacrylonitrile composite (WS2 –SPAN) was prepared using an electrospinning technology combined with a sulphuration process. By virtue of the abundant S vacancies and in situ N doping, the WS2 –SPAN composite shows an impressively ultralong lifespan and stable circulation capacity over a wide temperature range (−15–50 °C). For sodium storage, the WS2 –SPAN-2 composite delivers optimized high-rate performance and ultrastable cycling properties (464 mA h g −1 /450 cycles at 0.5 A g −1 ; 354 mA h g −1 /1400 cycles at 2 A g −1, 190 mA h g −1 /12 000 cycles at 5 A g −1 ; 129 mA h g −1 /18 000 cycles at 10 A g −1, surpassing previously reported WS2 -based anodes for SIBs). This is paired with an Na3 V2 (PO4 )3 cathode, which exhibits excellent storage capacity (241 mA h g −1 /200 cycles at 0.5 A g −1 ). Potassium storage also demonstrates admirable performance (362 mA h g −1 /100 cycles at 0.1 A g −1 ; 278 mA h g −1 /3000 cycles at 1 A g −1 ). In addition, a detailed illustration of the electrochemical storage mechanism of WS2 –SPAN composites is presented through theoretical calculations and electrochemical dynamics. Thus, the present investigation provides new insights into the preparation of novel WS2 -based anodes for sodium/potassium-ion batteries with ultralong lifespans and wide-temperature workability.